Consumer protection enforcement law characteristics on civil law aspects in Indonesia - Syam, Misnar; Ismansyah, Ismansyah; Azheri, Busyra; Hasbi, Muhammad (Linguistics and Culture Review, 2021)
Law enforcement on consumer protection reflects the norms or rules of consumer protection law that apply in the community to be obeyed. The use of law enforcement instruments in consumer protection is a civil lawsuit that can be made by consumers, either individually or in groups, non-governmental organizations and the government. Consumer protection is something that is very important, because basically all humans are consumers. This consumer protection has been regulated in Law Number 8 of 1999 concerning Consumer Protection (hereinafter referred to as UUPK). The purpose of this law is to balance the rights and obligations of consumers and actors so as to provide protection to both parties, even though the interests of consumers and business actors are different. This difference in interests can trigger disputes between consumers and business actors. This consumer protection law enforcement can be done in court or out of court. Law enforcement on consumer protection is currently weak and tends to weaken. This can be seen from the number of complaints, complaints and consumer disputes submitted through social media, the voices of readers and those that go to BPSK, BPKN, LPKSM and YLKI, but very few get to the court process.